1990
DOI: 10.1002/hon.2900080406
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features associated with transformation of cerebriform T‐cell lymphoma to a large cell process

Abstract: Some patients with cerebriform T-cell lymphoma (CTCL) undergo morphologic transformation to a large cell lymphoma. From a series of 113 patients with CTCL, 22 patients were identified with transformed CTCL. Stages of involvement at diagnosis were: I (seven), II (four), III (four), IV (seven). Nine patients had transformation at the initial diagnosis while the median time from diagnosis to transformation in the other 13 patients was 16 months (range: 3 months-6 years). Thirteen had transformation extracutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 61 publications
2
54
4
Order By: Relevance
“…In addition to staging, male gender, increasing age, an elevated LDH and the folliculotropic variant of MF were also independently associated with poorer overall and disease-specific survival. In contrast to previous reports highlighting the aggressive clinical course associated with large cell transformation [189][190][191][192][193], defined as the presence of large, atypical lymphocytes comprising at least 25% of the total lymphoid infiltrate, large cell transformation was not an independent predictor of overall or disease-specific survival but was associated with a higher risk (hazard ratio 3.32) of disease progression [7]. Given the importance of the TNMB classification in risk stratification and defining disease burden, the ISCL/EORTC recommends its use in defining the initial, maximum and current burden of disease, which will ultimately play an important role in the selection of either skin-directed or systemic therapies [143].…”
Section: Risk-stratification Stagingcontrasting
confidence: 73%
“…In addition to staging, male gender, increasing age, an elevated LDH and the folliculotropic variant of MF were also independently associated with poorer overall and disease-specific survival. In contrast to previous reports highlighting the aggressive clinical course associated with large cell transformation [189][190][191][192][193], defined as the presence of large, atypical lymphocytes comprising at least 25% of the total lymphoid infiltrate, large cell transformation was not an independent predictor of overall or disease-specific survival but was associated with a higher risk (hazard ratio 3.32) of disease progression [7]. Given the importance of the TNMB classification in risk stratification and defining disease burden, the ISCL/EORTC recommends its use in defining the initial, maximum and current burden of disease, which will ultimately play an important role in the selection of either skin-directed or systemic therapies [143].…”
Section: Risk-stratification Stagingcontrasting
confidence: 73%
“…CTCL to be between 11% and 23%. [5][6][7][8] The incidence of transformation in our CTCL database is just 6.1% using the same diagnostic criteria. Transformation was much more common in patients with a more advanced stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] LCT is pathologically characterized by the morphologic change of small-to mediumsized cerebriform cells to a large cell variant, 11 accompanied by clinically aggressive disease. Large cells are lymphocytes that are at least 4 times greater in size than a small lymphocyte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because all but these two follow-up biopsies had been obtained from patients without evidence of extracutaneous disease at the time of biopsy the clinical stage was determined only by the type of skin lesions, defined as the presence of patches and plaques covering more than 10% of the skin surface (T2) or the presence of tumors (T3). Because previous studies demonstrated unequivocally that skin tumors showing blastic transformation have a significantly worse prognosis than tumors without blastic transformation 23,24 within the T3 category, distinction was made between tumors with and tumors without blastic transformation, defined by the presence of more than 50% blast cells. Therefore, we will refer primarily to the type of skin lesion (patches/plaques, tumors without, and tumors with blastic transformation).…”
Section: Patientsmentioning
confidence: 99%